Could an interactive medium introduce non-practitioners to mindfulness meditation? - Vidyarthi, Jay; Riecke, Bernhard E. (First International Conference on Mindfulness, 2013)
INTRODUCTION: To many non-practitioners, the importance of mindfulness meditation is easily overshadowed by contemporary media-saturated societies. In contrast to emerging biofeedback applications which emphasize self-monitoring for existing practitioners, we designed an interactive medium which aims to provide a compelling, contemplative experience for those non-practitioners who share a widespread obsession with new technology. "Sonic Cradle" has already been well-received by technologists; this submission holds an explicit goal of getting feedback from the mindfulness community. METHODS: "Sonic Cradle" suspends non-practitioners in a completely dark sound chamber where they are able to summon and modulate peaceful audio recordings simply through respiration. As attention inevitably wanders from awareness to distraction, the breath-controlled soundscape subtly encourages a calm return to internal focus. This study explores how experiences in "Sonic Cradle" compare to the intimate practice of mindfulness meditation using a systematic qualitative investigation involving 3 independent data coders and 39 naïve participants. RESULTS: The study revealed 11 findings which are each discussed both quantitatively and descriptively, including mental clarity, loss of intention, perceptual illusions, and emotional responses. Rigorous criteria ensure that each finding represents a numeric consensus across independent coders and participants. DISCUSSION: Findings suggest that Sonic Cradle consistently induced experiences comparable to academic understanding of mindfulness meditation. While obviously not a replacement for this vital practice, this first investigation supports research on new approaches to persuading technophilic non-practitioners to independently consider self-regulating through mindfulness meditation. Cultivating an early glimpse of an advanced experience will motivate adoption and adherence in this age of wandering attention.
Keywords: Riecke; Riecke_2013; jay-vidyarthi; sonic-cradle; talkWithoutPaper